Ethephon on the growth of squash plants in protected environment - Iozi, Ricardo Neiva; Rodrigues, João Domingos; Ono, Elizabeth Orika; Goto, Rumy (Semina: Ciências Agrárias, 2000)
<!--[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman";} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> The aim of this work was to study the effect of Ethephon on the growth of squash plants, under conditions of protected environment. The application of Ethephon at 200 and 400 mgt1, was carried out in two stages of development, 2nd and 4th true leaf. The growth of the plants was evaluated with the following parameters of the growth analysis: Leaf Area Ratio (g.g1) - LAR; Specific Leaf Area (cm2.g1) - SLA; Leaf Mass Ratio (9-91) - LMR; Relative Growth Rate (g.g-1 .day1) - RGR and Net Assimilation Rate (g.cm2.day1) - NAR. The LAR increased from the first to the second collect to decreased soon after that, being that the Ethephon 400 mg.L1 applied in the stage of 4th true leaf presented difference to the 57 DAS (days after seeding). The SLA curves are increasing in the beginning of the development, presenting reduction through the long of the cycle. How much the LMR all the treatments had presented similar behaviour, not evidencing effect of Ethephon application. Ethephon 200 mg.L1 applied in the stage of 4th true leaf presented constant values of RGR. All the treatments had presented at least two peaks of NAR values and except for control, showed decreasing results in the last interval.